The Meaning of Motivation in the Lyrics of Manusia Kuat by Tulus (Ferdinand De Saussure's Semiotic Analysis) - Syarief, Fauzi; Putra, Jaqualine Pramanta; Kasmir, Mursyid; Susana, Susana (Sean Institute, 2025)
Song as a medium of communication not only conveys messages in an aesthetic manner but is also rich in profound meanings that can be analyzed through a semiotic approach. This study aims to reveal the motivational meanings contained in the lyrics of Manusia Kuat by Tulus using Ferdinand de Saussure’s semiotic framework. This approach examines signs through two main elements, namely the signifier and the signified, in order to uncover the relational meaning within the structure of the lyrics. The findings indicate that the song embodies strong motivational messages, such as perseverance, resilience, and confidence in human strength when facing life’s challenges. Lyrics such as “kita ini manusia kuat” and “kamu bukan debu yang diam” represent symbols of spirit and self-empowerment. In conclusion, through its linguistic symbols and connotative meanings, Manusia Kuat successfully articulates motivation that inspires listeners to become resilient and optimistic individuals.